Measuring Business Model Innovation Performance of Food and Beverage Industry: A Study of SMEs In Bogor City - Habibullah Habibullah; Illah Sailah; Elisa Anggraeni (Syntax Corporation, 2022)
Business model innovation is a business practice tool to develop a business competitive advantage. Extensive research on the business model has resulted in wide definition, conceptualization, and its multi case-based results. But there is still a lack of study in measuring the business models as proof of its performance. This study fills the gap by analyzing the business model innovation performance in special cases of food and beverage small and medium industries (SMIs) in Bogor City and finding room improvement to increase their performance. This study uses practical business model performance analysis with three dimensions acquired by a rigorous approach from the previous study. As a result, this measuring method shows the performance of food and beverage SMIs Bogor City mostly innovative. However, there are some improvements needed to increase the performance in element new capability, new channel, and new revenue model.